Metagenomic Analysis Reveals New Microbiota Related to Fiber Digestion in Pigs - Liu, Gensheng; Li, Pinghua; Hou, Liming; Niu, Qing; Pu, Guang; Wang, Binbin; Du, Taoran; Kim, Sung Woo; Niu, Peipei; Li, Qiang; Huang, Ruihua (Frontiers in Microbiology, 2021)
Making full use of high fiber and low-cost crop coproducts is helpful to alleviate the situation of people and livestock competing for crops. Digestion of dietary fibers in pigs is mainly through microbial fermentation in the large intestine. To reveal more microbiota related to fiber digestion in pigs, fecal samples have been collected from 274 healthy female Suhuai pigs at 160 d of age under the same feeding conditions and have measured apparent neutral detergent fiber (NDF) and acid detergent fiber (ADF) digestibility. Samples from Suhuai pigs with ex-treme high (H_NDF, n=5) and low (L_NDF, n=6) apparent NDF digestibility and extreme high (H_ADF, n=6) and low (L_NDF, n=6) apparent ADF digestibility were subjected to shotgun metagenomic sequencing. At the species level, 62 microbial species in H_NDF group and 54 microbial species in H_ADF group were related to high fiber digestibility. Among them, Lachnospiraceae bacterium 3-1, Alistipes sp. CAG:514 and Eubacterium sp. CAG:115 are new type of microorganism related to fiber digestion. In addition, the relative abundance of gene families with cellulose (GH5 and GH48 in NDF group; GH3 and GH9 in ADF group), hemicellulose (GH39 and GH53 in NDF group), and lignin (AA4 in two groups) degrading activity were different in the extreme high and low apparent fiber digestibility groups. High apparent fiber digestibility group had increased relative abundance of 7 pathways related to degradation of non-starch polysaccharides compared with low apparent fiber digestibility group. Gut microbiota of Suhuai pigs with high apparent fiber digestibility had higher abundance of genes and microbiota related to fiber digestion and had stronger fiber digestion potential compared with low apparent fiber digestibility group. To fully understand the relationship between microbiota and pig fiber digestion ability is helpful for the extensive application of high fiber and low-cost crop coproducts in pig feed in the future.